Design and Implementation of a Reliable and Secure Controller for Smart Home Applications Based on PLC - Khairullah, Shawkat Sabah; Sharkawy, Abdel-Nasser (Universitas Muhammadiyah Yogyakarta, 2022)
Programmable logic controllers (PLCs) are increasingly being used to realize modern safety-critical instrumentation and control (IC) applications. Examples of these applications are industrial automation and control systems, plant process safety protection systems, smart home systems and digital IC systems embedded in nuclear power plants (NPPs) that require high levels of performance, reliability, and flexibility. The PLC is a flexible, programmable, and robust digital device that can execute all logical and mathematical runtime functions of the IC application and operate in harsh-critical environments. This paper proposes a PLC-based home security controller based on the ladder logic programming model. The design, analysis, and hardware implementation of this controller are presented in this paper. The designed system consists of three basic modules which are a sensing module used for reading the data of the input field devices for the smart home application, a computation-based decisional module used for executing the programming model, and an actuating module used for sending the control commands to the output field devices. The proposed home security system utilized different types of sensors such as a laser photoelectric sensor, a motion or proximity sensor, and a limit switch. In addition, a siren speaker, a light tower including three lights red, yellow, and green, two push-pull switches and emergency push-pull buttons were used as control inputs and output indicators in the implementation of this work This designed system is implemented on the Allen-Bradley CompactLogix PLC controller and Human Machine Interface (HMI) panel programmed as the graphical user interface. The experimental simulation results of the real hardware connection demonstrate that the proposed system is reliable, safe, and feasible for smart home security applications.